Analgesia After Cesarean Delivery in the United States 2008-2018: A Retrospective Cohort Study. Issue 2 (24th June 2022) - Reed, S.E.; Tan, H.S.; Fuller, M.E.; Krishnamoorthy, V.; Ohnuma, T.; Raghunathan, K.; Habib, A.F.
Abstract : ( Anesth Analg . 2021;133:1550–1558) Multimodal, opioid-sparing analgesia is currently recommended for postcesarean pain management in the United States. These regimens combine neuraxial morphine, scheduled nonsteroidal anti-inflammatory drugs (NSAIDs) and scheduled acetaminophen. Recent studies have supported the use of scheduled acetaminophen plus opioids on an as-needed basis rather than acetaminophen-opioid combination drugs. This study aimed to investigate analgesia following cesarean delivery under neuraxial anesthesia in the United States and examine variations in analgesic regimens over time and between institutions.